Outbreak of Salmonella food poisoning in a training institute: an epidemiological approach - Singh, Man; Minhas, Sukhmeet; Singh Parda, Maninder Pal; Ahmed, Shafique; Nimonkar, Ravi (International Journal Of Community Medicine And Public Health, 2025)
Background: On 04th April 2020 night report was received from the local hospital that 32 students from the training institute had reported, with complaints of diarrhea; and fever. The investigation team reported to the training institute. Objectives of this investigation were as follows: (a) To identify the incriminating food item(s), (b) To identify the factors leading to food contamination, (c) To identify the agent responsible for the outbreak. Methods: The study design was a retrospective descriptive epidemiological study. The study population included students dining in the Mess; and staff. Epidemiological investigation was conducted using descriptive epidemiology. Stool samples of cases, samples of prepared meals; and water samples from the Mess were sent for bacteriological examination. Hygiene of the mess, supply chain, personal hygiene of food handlers; and relevant documents were checked. Results: Total 116 cases reported during the outbreak with two peaks. All cases were dining in the Mess. All cases had diarrhoea; and 75 (64.65%) had abdominal pain. 109 (93.96%) cases were treated as outpatients. Average duration of illness was 2-3 days. Refrigeration of egg storage was defunct. Laboratory reports were positive for coliforms in rajma, milk and chicken curry. Epidemiologically, the incriminated food item was found to be egg bhurji as per attack rate and relative risk. Clinico-epidemiologically, cause of this food poisoning appears to be Salmonella. Conclusions: Detailed epidemiological investigations, laboratory investigations and environmental survey was carried out. Clinico-epidemiologically the causative organism was suspected to be Salmonella due to consumption of contaminated egg bhurji.